2007
DOI: 10.1021/jm0614376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Diamine Nonleaving Group in Platinum−Acridinylthiourea Conjugates on DNA Damage and Cytotoxicity

Abstract: The following complexes of type [PtCl(R)(ACRAMTU)](NO3)2 (ACRAMTU = 1-[2-(acridin-9-ylamino)ethyl]-1,3-dimethylthiourea)), derived from prototype 1 (with R = ethane-1,2-diamine), were synthesized: 2 (with R = (1R,2R)-1,2-diaminocyclohexane), 3 (with R = propane-1,3-diamine), 4 (with R = N1,N1,N2,N2-tetramethylethane-1,2-diamine), and 5 (with R = 2,2'-bipyridine). The DNA sequence specificity of the conjugates and their antiproliferative potential in HL-60 and H460 cells were investigated. Conjugate 3 showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 28 publications
2
58
0
Order By: Relevance
“…Azido and hydroxido ligands can dissociate from trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (Am1)(Am2)] complexes upon irradiation with light, and Am1 and Am2 remain as non-leaving groups 38. The current work reveals the similarities between 1 and 5 , and between 2 and 6 (Table 4).…”
Section: Discussionmentioning
confidence: 54%
“…Azido and hydroxido ligands can dissociate from trans , trans , trans -[Pt(N 3 ) 2 (OH) 2 (Am1)(Am2)] complexes upon irradiation with light, and Am1 and Am2 remain as non-leaving groups 38. The current work reveals the similarities between 1 and 5 , and between 2 and 6 (Table 4).…”
Section: Discussionmentioning
confidence: 54%
“…282287 Polymerase stop assays and flow cytometric assays showed that the hybrid adducts inhibited RNA polymerase II and DNA synthesis. 285,286,288 Inhibition of DNA synthesis led to S phase cell cycle arrest as opposed to G2/M phase cell cycle arrest, as is customary following cisplatin treatment. 288 Although Pt-ACRAMTU maintained sub-micromolar activity in cell lines with aberrant p53 and k-ras expression, because of their inability to stop tumor growth in corresponding tumor mouse models, preclinical development was halted and other Pt-ACRAMTU analogues have been subsequently investigated.…”
Section: Platinum(ii) Compounds With a Mechanism Of Action Differementioning
confidence: 99%
“…201,202 Although the first generation analogues of these complexes with underivatized thiourea ligands exhibit only poor to moderate in vitro cytotoxicity, 203 the second generation compounds with acridine-functionalized thioureas are typically more cytotoxic than cisplatin. 174,204,205 These Pt-acridinylthiourea, or PT-ACRAMTU, conjugates form hybrid DNA adducts; 206 the Pt center binds preferentially to N 7 of guanine bases and the acridine intercalates between base pairs. Several dichloridoplatinum(II) complexes tethered to acridine through a modified ethylenediamine ligand, first reported in the late 1980s, also exhibit dual intercalation and covalent DNA-binding modes.…”
Section: Synthesis Of Platinum(ii) Complexesmentioning
confidence: 99%